2015
DOI: 10.1371/journal.pone.0130624
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Is Expressed and Functional in Mouse Brain Microglia but Not in Astrocytes

Abstract: Neuroinflammation is the local reaction of the brain to infection, trauma, toxic molecules or protein aggregates. The brain resident macrophages, microglia, are able to trigger an appropriate response involving secretion of cytokines and chemokines, resulting in the activation of astrocytes and recruitment of peripheral immune cells. IL-1β plays an important role in this response; yet its production and mode of action in the brain are not fully understood and its precise implication in neurodegenerative diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
218
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(251 citation statements)
references
References 54 publications
20
218
0
3
Order By: Relevance
“…Halle et al demonstrated that the phagocytosis of ibrillar Aβ activates NALP3 inlammasomes in mouse microglia. The activation of NALP3 was dependent on lysosomal damage and cathepsin B release, as was observed earlier in the crystal-induced NALP3 activation [75,76]. Then, more evidence was supportive for that Aβ activate the NLRP3 inlammasome in microglial cells in vitro and in vivo [77][78][79].…”
Section: Il-1r Signaling and Inlammasomesupporting
confidence: 64%
“…Halle et al demonstrated that the phagocytosis of ibrillar Aβ activates NALP3 inlammasomes in mouse microglia. The activation of NALP3 was dependent on lysosomal damage and cathepsin B release, as was observed earlier in the crystal-induced NALP3 activation [75,76]. Then, more evidence was supportive for that Aβ activate the NLRP3 inlammasome in microglial cells in vitro and in vivo [77][78][79].…”
Section: Il-1r Signaling and Inlammasomesupporting
confidence: 64%
“…There are a plethora of studies that demonstrates NLRP3 activation in bone-marrow derived macrophages and dendritic cells (Burm et al, 2015); however, only scant evidence are available regarding the mechanisms regulating the priming and activation of NLRP3 inflammasome in the microglia (Gustin et al, 2015). In the present study, we investigated the inflammatory mechanisms involved in ROT-stimulated LPS-primed microglia using BV2 microglial cell line and mouse primary microglia.…”
Section: Introductionmentioning
confidence: 99%
“…Tan and coworkers demonstrate Heneka, et al [37] NLRP3 -/-and Caspase-1 -/-mice are resistant to experimentally developed AD Griffin, et al [28] IL-1β induces tau protein hyperphosphorylation Gustin, et al [42] Aβ stimuli activate NLRP3 specifically in microglia Wu, et al [45] Aβ protofibrils induce NLRP3 activation and IL-1β accumulation in microglia Couturier, et al [38] ASC -/-mice are resistant to experimentally developed AD Clinical study…”
Section: Microglia Nlrp3 and Alzheimermentioning
confidence: 99%
“…In AD, little is known about NLRP3 activation mechanisms in the CNS during the course of the disease. In experiments using Aβ as NLRP3 stimulus as well as known inflammasome agonists such as ATP and nigericin, Gustin and coworkers indicated that NLRP3 machinery is only present in microglia, at least in some circumstances, and not in astrocytes, reinforcing the crucial role of microglial NLRP3 activity in CNS [42]. However, other studies disagree with these findings and suggest NLRP3 activation in astrocytes after CNS injury.…”
Section: Nlrp3 Pathway As a Target For Ad Treatmentmentioning
confidence: 99%